A new species of Varronia (Cordiaceae) from Brazil and first record of V. spinescens for Amazonas State - Alan Tamagawa; José Iranildo Miranda de Melo (Kew Bulletin, 2026)
Summary Varronia fluviatilis Tamagawa & J.I.M.Melo (Cordiaceae), a new species restricted to the semiarid region of north-eastern Brazil, is described and illustrated. Varronia spinescens (L.) Borhidi, previously known in Brazil only from Pará State, was recorded for the first time in Amazonas State, both situated in northern Brazil. A provisional conservation assessment for V. fluviatilis is provided, as well as a key to distinguish it from other Varronia representatives from the Caatinga phytogeographical domain. These results increase to fourteen the number of species of Varronia in the Caatinga, and to seven the number in Amazonas State.